2005
DOI: 10.4028/www.scientific.net/msf.502.243
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Oxidation Resistance of NbSi<sub>2</sub> by Addition of Boron

Abstract: Abstract. NbSi 2 is a promising candidate as a coating material for Nb-base alloys. However, it shows complicated oxidation behavior, depending on oxidation temperature. In the present study, in order to clarify the oxidation resistance of NbSi 2 , oxidation tests of sintered NbSi 2 were carried out at temperatures ranging from 773 to 1673 K in air. Moreover, the effect of addition of boron on oxidation resistance of NbSi 2 was clarified. NbSi 2 showed accelerated oxidation at temperatures of 1073 K and above.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Kurokawa et al [30] reported that bulk NbSi 2 has a complex oxidation behavior depending on oxidation temperature, but showed satisfactory oxidation resistance between 1000 and 1100 C. The complex oxidation behavior of the bulk NbSi 2 was probably due to voids and micro-cracks produced during its preparation.…”
Section: Oxidation Behavior Of Nbsi 2 /Nb/g-tial In Airmentioning
confidence: 96%
“…Kurokawa et al [30] reported that bulk NbSi 2 has a complex oxidation behavior depending on oxidation temperature, but showed satisfactory oxidation resistance between 1000 and 1100 C. The complex oxidation behavior of the bulk NbSi 2 was probably due to voids and micro-cracks produced during its preparation.…”
Section: Oxidation Behavior Of Nbsi 2 /Nb/g-tial In Airmentioning
confidence: 96%
“…This is probably due to the formation of a borosilicate layer having higher plasticity than silica, in addition to improvement of adhesive bonding of oxide scale to substrate. In fact, we demonstrated that addition of boron into NbSi 2 leads to outstanding improvement of oxidation resistance of NbSi 2 [11]. Therefore, Nb-base alloys coated with NbSi 2 -B can be fully recognized to be promising candidate materials for ultra-high temperature applications.…”
Section: Introductionmentioning
confidence: 94%
“…Future high-temperature structural applications will require materials with increasing performances. This is the reason why intermetallics, [1][2][3][4] ceramics, 5) carbon composites, [6][7][8] and refractory metals 9,10) are candidates for replacing the current Ni-base superalloys. Silicide becomes one of the above candidates, because it has high strength and can form a protective SiO 2 scale at very high temperature.…”
Section: Introductionmentioning
confidence: 99%
“…17) According to Kurokawa et al, the oxidation resistance of NbSi 2 is dramatically improved by the addition of B with concentrations of 2 mass% or higher at temperatures ranging from 1073 to 1673 K in air. 4) Consequently, their results suggested that the formation of a borosilicate scale having high plasticity suppressed the high porosity of the scale, making the scale much more protective. 4,17,18) The purpose of this work is to clarify the effect of B addition on the improvement of oxidation resistance for WSi 2 compacts, especially at intermediate temperatures (1073-1473 K).…”
Section: Introductionmentioning
confidence: 99%